Performance of the Human Papillomavirus E6/E7 mRNA Assay in the Primary Screening of Cervical Cancer: Opportunistic Screening in Fujian, China - Zhuang L; Weng X; Wang L; Xie X; Zhong L; Liu D; Xiu Y (Dove Medical Press, 2022)
Lijuan Zhuang *, Xiulan Weng *, Lihua Wang, Xiaoyan Xie, Liying Zhong, Dabin Liu, Yingling Xiu Department of Obstetrics and Gynecology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Yingling Xiu; Dabin Liu, Department of Obstetrics and Gynecology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, 18 Daoshan Road, Fuzhou, People's Republic of China, Tel +86-13860610354 ; +86-13489997701, Fax +86-591-87551247, Email xiuyingling@fjmu.edu.cn; xiuyingling1985@163.com; 15968250@qq.comPurpose: A high-risk human papillomavirus E6/E7 mRNA (HR-HPV mRNA) assay is widely used in cervical cancer screening in China. However, it is still unclear whether stand-alone HR-HPV mRNA testing is sufficient for primary screening. The purpose of this study was to investigate the feasibility of a stand-alone HR-HPV mRNA assay for primary screening of cervical cancer.Methods: Women aged 21 and older were recruited in Fujian Province, China, from January 2020 to January 2022. Cervical exfoliated cells were collected for cervical cytology and HR-HPV mRNA assays, and women with positive results on either assay were referred for colposcopy. The screening effectiveness of the assay was calculated based on the cervical histology. When comparing the efficacy of the different screening strategies, only women aged 25 and older were included.Results: A total of 9927 women were recruited. This study identified 217 cases of high-grade squamous intraepithelial disease or worse (HSIL+). The overall age-specific HR-HPV infection rate showed a U-shaped distribution. The sensitivity of the HR-HPV mRNA assay to identify CIN2+ and CIN3+ was 97.2% and 97.9%, respectively, which was significantly higher than that of cytology (82.9% and 88.6%, P< 0.001 and 0.002). The sensitivity of the HR-HPV mRNA primary screening strategy to identify CIN2+ and CIN3+ was 92.2% and 94.3%, respectively, which was similar to the co-testing strategy (P=0.336 and 0.394) and higher than the cytology primary screening (P=0.002 and 0.048). In addition, the HR-HPV primary screening strategy had a lower referral rate for colposcopy than cytology primary screening (5.4% vs 6.6%, P< 0.001), and the screening cost was lower than co-testing ($29,594.3 per 1000 screened women vs $55,140 per 1000 screened women, P< 0.001).Conclusion: In conclusion, the detection of CIN2+/CIN3+ by HR-HPV mRNA is both specific and sensitive. It may be suitable for primary screening of cervical cancer in China.Keywords: cervical cancer, HR-HPV, E6/E7 mRNA, primary screening, cervical intraepithelial neoplasia